Step (1): Assume given statement
Let the given statement be P(n), i.e,
P(n):a+ar+ar2+⋯+arn−1=a(rn−1)r−1
Step (2): Checking statement P(n) for n=1
Put n=1 in P(n), we get
P(1):a=a(r1−1)r−1
⇒a=a
Thus P(n) is true for n=1.
Step (3): P(n) for n=K
Put n=K in P(n) and assume this is true for some natural number K i.e,
P(K):a+ar+ar2+⋯+arK−1=a(rK−1)r−1 ⋯(1)
Step (4): Checking statement P(n) for n=K+1
Now we shall prove that P(K+1) is true whenever P(K) is true.
Now, we have
a+ar+ar2+⋯+arK−1+arK
=(a+ar+ar2+⋯+arK−1)+arK
=a(rK−1)r−1+arK (using 1)
=arK−a+arK(r−1)r−1
=arK−a+arK+1−arKr−1
=arK+1−ar−1
=a(rK+1−1)r−1
Thus, P(K+1) is true whenever P(K) is true.
Final answer :
Therefore, by the principle of mathematical induction statement P(n) is true for all n∈N.